2012
DOI: 10.1021/bi300876h
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Release Sequences in the Protein Kinase SRPK1 Accelerate Substrate Phosphorylation

Abstract: Protein kinases are essential signaling enzymes that transfer phosphates from bound ATP to select amino acids in protein targets. For most kinases, the phosphoryl transfer step is highly efficient while the rate-limiting step for substrate processing involves slow release of the product ADP. It is generally thought that structural factors intrinsic to the kinase domain and the nucleotide-binding pocket control this step and consequently the efficiency of protein phosphorylation for these cases. However, the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…kdSRPK1, inactive SRPK1 containing K109M, was expressed and purified from a pET19b vector. Deletion constructs SRPK1(ΔN), SRPK1(ΔS) and SRPK1(S) (residues 222-492) were expressed and purified as previously described (Aubol et al, 2014; Aubol et al, 2012). CLK1 virus was transfected and expressed in Hi5 insect cells and CLK1 was purified with a Nickel resin and a published procedure (Keshwani et al, 2015b).…”
Section: Methodsmentioning
confidence: 99%
“…kdSRPK1, inactive SRPK1 containing K109M, was expressed and purified from a pET19b vector. Deletion constructs SRPK1(ΔN), SRPK1(ΔS) and SRPK1(S) (residues 222-492) were expressed and purified as previously described (Aubol et al, 2014; Aubol et al, 2012). CLK1 virus was transfected and expressed in Hi5 insect cells and CLK1 was purified with a Nickel resin and a published procedure (Keshwani et al, 2015b).…”
Section: Methodsmentioning
confidence: 99%
“…SRPK cellular partition is regulated, at least in part, by the unique spacer domain in each SRPK family member, as deletion of the spacer shifts the kinase to the nucleus (Ding et al, 2006; Ngo et al, 2008; Nolen et al, 2001). Initial evidence suggests that the spacer has little effect on the kinase activity, but a more recent study indicates that it can enhance the catalysis by increasing the rate-liming ADP release step in the kinase reaction (Aubol et al, 2012). In contrast, all Clk family members are constitutively localized in the nucleus and show extensive colocalization with SR proteins in nuclear speckles (Colwill et al, 1996b; Duncan et al, 1998).…”
Section: Regulation Of Sr Proteins By Post-translational Modificationsmentioning
confidence: 99%
“…21 To evaluate whether the RS2 segment functions as a molecular trigger for activation through the NRF or possibly through other sequences in the SID, we investigated SR(RS2)-dependent changes in the phosphorylation of SR(ΔRS2) using several truncated forms of SRPK1 (Figure 4A). We initially showed that SR(RS2) did not increase the maximal velocity of SRPK1(ΔN) or SRPK1(ΔS) consistent with the idea that RS2 enhances catalysis through sequences in the N-terminus and SID (Figure 4D and Table 2).…”
Section: Resultsmentioning
confidence: 99%